Une géopolitique des classes ? - Stéphane Rosière (L'Espace Politique)
This paper aims to discuss the possibility to set a geopolitics of social classes. This geopolitical theory may be sketched as a struggle between a dominant class (world oligopoly) that symbolize the center of World-system and a dominated class gathering poor people located at the periphery. This paper explains first why this refexion never grew up. Indeed, geopolitics was, first of all, the science of imperialism and never paid attention to social classes. Then, the author tries to define which elements could constitue a ‘geopolitics of social classes’. The dominant position of ologopoly may endure only in a certain organisation/production of space. This organisation/production is more or less indifferent to territorial fragmentation into states, but it is very sensitive to hierarchy and control of places and to networks structuration at global and local scales. The author reviews the condition of this domination/production at the global scale – mostly through the United States politics example – and at the local scale considering mostly the structure of contemporary cities. The significance of social violence seems to be more accurate in a world where interstates violence (wars) is decreasing. Social ‘class’ factor seems to play a role in inverse proportion with national factor which is the base of international relations. The transition from interstate roughness to interclasses roughness could be one of the contemporary characteristic of a social classes geopolitics, or a "radical" geopolitics.